2015
DOI: 10.1590/1980-57642015dn93000013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life and psychological aspects of Parkinson's disease patients who participate in a support group

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder that can dramatically impair patient quality of life (QoL).ObjectiveTo analyze the QoL, motor capacity, depression, anxiety and social phobia of individuals who attended a patient support group (PSG) compared to non-participants.MethodsA cross-sectional study was performed. The sample consisted of 20 individuals with PD who attended a PSG and another 20 PD patients who did not attend a support group for PD patients, serving as the control group (nPSG). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A study from the city of Porto Alegre in Southern Brazil, carried out in the entire population, found lower quality of life scores among those that reported depression and anxiety in all domains measured by WHOQOL-BREF (p-value < 0.001) 32 . In another study in the same city, patients with Parkinson's disease that participated in a support group presented better quality of life (p = 0,002), less depression (p = 0,026), less anxiety (p < 0,001) and social phobia (p = 0,01) than those that did not come to the group 33 . A further study, from London (England), found higher quality of life scores in the presence of a social support network in the case of psychotic patients 14 .…”
Section: Discussionmentioning
confidence: 92%
“…A study from the city of Porto Alegre in Southern Brazil, carried out in the entire population, found lower quality of life scores among those that reported depression and anxiety in all domains measured by WHOQOL-BREF (p-value < 0.001) 32 . In another study in the same city, patients with Parkinson's disease that participated in a support group presented better quality of life (p = 0,002), less depression (p = 0,026), less anxiety (p < 0,001) and social phobia (p = 0,01) than those that did not come to the group 33 . A further study, from London (England), found higher quality of life scores in the presence of a social support network in the case of psychotic patients 14 .…”
Section: Discussionmentioning
confidence: 92%
“…Several participants in Uebelacker et al's survey indicated peer support groups are helpful ( 13 ). A cross-sectional study reported that attending a support group is associated with better quality of life and reduced depression and anxiety for PD patients ( 43 ). Cognitive behavioral therapy (CBT) has been investigated for addressing depression and anxiety in PD in several clinical trials with promising results ( 44 48 ).…”
Section: Non-medical Strategies For Coping With Tremormentioning
confidence: 99%
“…Social relationships with family, friends, and support groups-specifically, effective communication and acceptanceare necessary to maintain QoL in PWP (29,30). Coping with the progression of PD presents challenges that may be relieved through support groups, thus improving QoL, depression, and anxiety in PWP (31). Although in-person support groups are common practice for managing the neuropsychiatric symptoms of PD (32), during the COVID-19 pandemic, barriers such as social distancing and shelter-in-place orders rendered in-person programs unavailable.…”
Section: Mental Health In Parkinson's Diseasementioning
confidence: 99%
“…The aims of vSG were to maintain social connections and to positively influence QoL (25,31). Other aims included the provision of timely and accurate information about the pandemic (28,40), thus providing a forum for participants to discuss concerns and fears regarding the pandemic and its potential impact on their health.…”
Section: The Psychological Importance Of Social Connections: Vsg and ...mentioning
confidence: 99%